HE LIVES IN A PINEAPPLE UNDER THE SEA: subjectivity and work - Oliveira, Felipe (2020)
Filmography is the art that facilitates the construction of a connection between theoretical subjects and the practical reality of a determinated situation, through the use of films, cartoons and even series. In children's drawing SpongeBob SquarePants, we perceive a very detailed and rich business environment for study, so one wonders how the idea of ​​subjectivity and work in SpongeBob is portrayed? This research aimed to verify how the idea of ​​subjectivity and work in a children's drawing is portrayed, well known to people of various age groups. To help this objective, this study adopts the following steps: bibliographic survey on the subjects; specific episode mapping and character analysis of the characters in the drawing. This research is applied, qualitative, abductive, deductive, explanatory, exploratory, descriptive, bibliographic, telematized and Ex Post Fact. With this, coming to the following conclusion, the characters of the film represent human characteristics, being the drawing a critique for society, thus becoming an allegory.